Coordinated control of pulse width modulation based AC link series compensator and power system stabilizers. (December 2016) - Safari, Amin; Shayeghi, Hossein; Shayanfar, Heidar Ali
Highlights: A novel dynamic index for greatest coordinated control is presented. The proposed algorithm based on nonlinear constrained optimization programming is used. The best proficiency of the proposed control is simulated on a 4-machine and 16-machine networks. As well as PWMSC and PSS compensated large scale systems. Abstract: This study suggests a novel and mathematical dynamic index for greatest coordinated control of Pulse Width Modulation based AC link Series Compensator (PWMSC) and Power System Stabilizers (PSS) in multi-machine networks. The planned new dynamic index is developed as a fitness function to reinforce the oscillations damping under totally different loading conditions. A nonlinear constrained optimization programming is applied for reducing the dynamic index based mostly from critical eigenvalues of the systems. The robustness of the coordinated control is reached directly through extending numerous loading conditions from that of the nominal case. The best proficiency of the proposed control is showed through simulations on a four-machine and sixteen-machine power networks for various conditions. Linear and nonlinear analysis presents the high priority of the suggested dynamic index in tuning of the parameters controller.